New records of subtidal benthic marine algae from the state of Veracruz, southern Gulf of Mexico - José Luis Godínez-Ortega; Pedro Ramírez-García; Alejandro Granados-Barba; Michael J. Wynne (Revista Mexicana de Biodiversidad)
New records of subtidal benthic marine algae from the State of Veracruz, the southern Gulf of Mexico, are presented, which include 7 species and 2 forms. The material was collected from 6 sampling forays at 4 locations between October 2013 and September 2017. The collection sites included the “Ana Elena” and “Riva Palacio” shipwrecks and some poorly explored reefs in the State of Veracruz, Mexico. The morphological characteristics of Hypoglossum simulans, Halymenia hancockii, Dictyota humifusa, Caulerpa sertularioides f. longiseta, Avrainvillea levis f. translucens, Udotea caribaea, U. dixonii, U. unistratea, and Anadyomene saldanhae are described. Information about the habitats and geographic distributions of these taxa is provided.